2001
DOI: 10.1016/s0885-3924(01)00248-2
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Knowledge of Pain in the Elderly

Abstract: The purpose of this study was to investigate nurses' knowledge of pain and pain management with respect to elderly persons. Registered nurses at several general hospitals and nursing homes were surveyed by questionnaire concerning their knowledge of pain management in the elderly. The findings indicated a significant knowledge deficit in this area. There were also significant differences in knowledge levels between general hospital nurses and those working in nursing homes. We conclude that more education abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 10 publications
3
39
0
4
Order By: Relevance
“…In addition, anxiety, confusion, sleep disturbance, delirium, and paranoia also result from unmanaged pain (Gélinas et al, 2004). Nurses' ability to identify and adequately manage pain is multifactorial and includes 1) ability to interpret verbal and non-verbal signs of pain, 2) cultural bias 3) knowledge gap and 4) excessive concern about administering pain killers (Sloman,et al , 2001). Narayan (2010) conducted a study and found that registered nurses under-assessed severe pain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, anxiety, confusion, sleep disturbance, delirium, and paranoia also result from unmanaged pain (Gélinas et al, 2004). Nurses' ability to identify and adequately manage pain is multifactorial and includes 1) ability to interpret verbal and non-verbal signs of pain, 2) cultural bias 3) knowledge gap and 4) excessive concern about administering pain killers (Sloman,et al , 2001). Narayan (2010) conducted a study and found that registered nurses under-assessed severe pain.…”
Section: Introductionmentioning
confidence: 99%
“…However, the research literature and this study have demonstrated significant knowledge deficits in this context. Registered nurses in the aged care setting, for example, know less than their acute and palliative care counterparts about pain management (Sloman et al 2001). The respondents in this study do not seem familiar with the central tenets of good palliative care -that pain is what the client says it is, that it is more effective to prevent pain than treat pain that has already occurred, and that drug addiction is not to be feared.…”
Section: Aged Care Nurses and Pain Managementmentioning
confidence: 80%
“…However, the literature clearly identifies that pain is common among older people, with an estimated 45% to 83% of nursing home residents experiencing substantial pain (Parmalee et al 1993;Forrest 1995). So while pain should never be considered normal in a healthy older person, they do suffer comparatively more pain from chronic conditions than the rest of the population (Sloman et al 2001). Moreover, up to 60% of nursing home residents also have dementia (Jorm 2001).…”
Section: Pain Management In Residential Aged Carementioning
confidence: 99%
“…Environmental factors include, for example, caregiver responsiveness (42), staff knowledge (43), and the availability and distribution of resources in the institutional care environment (44).…”
Section: Discussionmentioning
confidence: 99%